Review of current cell-penetrating antibody developments for HIV-1 therapy - Muhamad Alif Che Nordin; Teow, Sin Yeang * (MDPI, 2018)
The discovery of highly active antiretroviral therapy (HAART) in 1996 has significantly reduced the global mortality and morbidity caused by the acquired immunodeficiency syndrome (AIDS). However, the therapeutic strategy of HAART that targets multiple viral proteins may render off-target toxicity and more importantly results in drug-resistant escape mutants. These have been the main challenges for HAART and refinement of this therapeutic strategy is urgently needed. Antibody-mediated treatments are emerging therapeutic modalities for various diseases. Most therapeutic antibodies have been approved by Food and Drug Administration (FDA) mainly for targeting cancers. Previous studies have also demonstrated the promising effect of therapeutic antibodies against HIV-1, but there are several limitations in this therapy, particularly when the viral targets are intracellular proteins. The conventional antibodies do not cross the cell membrane, hence, the pathogenic intracellular proteins cannot be targeted with this classical therapeutic approach. Over the years, the advancement of antibody engineering has permitted the therapeutic antibodies to comprehensively target both extra- and intra-cellular proteins in various infections and diseases. This review aims to update on the current progress in the development of antibody-based treatment against intracellular targets in HIV-1 infection. We also attempt to highlight the challenges and limitations in the development of antibody-based therapeutic modalities against HIV-1.